Dari Kesadaran Teologis ke Praktik Pedagogis: Model Pendidikan Kristiani Multikultural Kontekstual di Halmahera - Demianus Ice (Sekolah Tinggi Teologi Kalvari Manado, 2026)
Abstract: Christian education in a multicultural society faces the challenge of remaining faithful to its theological identity while remaining relevant to a pluralistic reality. This article examines the gap between the church's theological awareness of its calling to peace and the pedagogical practices of faith education, which remain transmissive and normative within the Halmahera Evangelical Church (GMIH). Through an analytical-constructive literature review of educational theology, contextual theology, and multicultural pedagogy, this study shows that theological foundations, including creation theology, incarnation, trinity, and missio Dei, have not been systematically translated into curricula and educational strategies that are responsive to plurality. As a major contribution, this article presents a conceptual model of contextual multicultural Christian education that integrates five components: normative theological foundations, sociocultural context analysis, multidimensional goals for faith formation, integrative learning content, and dialogical pedagogical strategies. This model emphasises the need to shift from doctrinal transmission to dialogical, communal transformation as part of the church's ecclesial calling. Abstrak: Pendidikan Kristiani di masyarakat multikultural menghadapi tantangan untuk tetap setia pada identitas teologis sekaligus relevan dengan realitas plural. Artikel ini mengkaji kesenjangan antara kesadaran teologis gereja tentang panggilan perdamaian dan praktik pedagogis pendidikan iman yang masih bersifat transmisif-normatif dalam konteks Gereja Masehi Injili di Halmahera (GMIH). Melalui kajian pustaka analitis-konstruktif terhadap literatur teologi pendidikan, teologi kontekstual, dan pedagogi multikultural, studi ini menunjukkan bahwa fondasi teologis yang mencakup teologi penciptaan, inkarnasi, trinitas, dan missio Dei belum diterjemahkan secara sistematis ke dalam kurikulum dan strategi pendidikan yang responsif terhadap pluralitas. Sebagai kontribusi utama, artikel ini menawarkan model konseptual pendidikan Kristiani multikultural kontekstual yang mengintegrasikan lima komponen: landasan teologis normatif, analisis konteks sosial-budaya, tujuan formasi iman multidimensional, konten pembelajaran integratif, dan strategi pedagogis dialogis. Model ini menegaskan perlunya pergeseran dari transmisi doktrinal menuju transformasi komunal yang dialogis sebagai bagian dari panggilan eklesial gereja